2021
DOI: 10.1016/j.wjorl.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Current trends and applications in endoscopy for otology and neurotology

Abstract: There has been a rapid increase in endoscopic ear surgery for the management of middle ear and lateral skull base disease in children and adults over the last decade. In this review paper, we discuss the current trends and applications of the endoscope in the field of otology and neurotology. Advantages of the endoscope include excellent ergonomics, compatibility with pediatric anatomy, and improved access to the middle ear through the external auditory canal. Transcanal endoscopic ear surgery has demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Choi et al 30 found that minimally invasive tympanoplasty performed with an endoscope resulted in shorter operative times and less postoperative pain for the patient. The highly maneuverable tool enables excellent visualization and also allows everyone on the surgical team to gain a similar view of the operating field 16 . We found the average neck angles to be comparable between microscopic and endoscopic surgery with the caveat of increased time spent in neck extension when using a microscope.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Choi et al 30 found that minimally invasive tympanoplasty performed with an endoscope resulted in shorter operative times and less postoperative pain for the patient. The highly maneuverable tool enables excellent visualization and also allows everyone on the surgical team to gain a similar view of the operating field 16 . We found the average neck angles to be comparable between microscopic and endoscopic surgery with the caveat of increased time spent in neck extension when using a microscope.…”
Section: Discussionmentioning
confidence: 64%
“…Endoscopes are emerging as indispensable tools in minimally invasive otology procedures 16 . Choi et al 30 found that minimally invasive tympanoplasty performed with an endoscope resulted in shorter operative times and less postoperative pain for the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EES has gained popularity over the last years, due to its advantages, which include a wide field of view, magnified vision, and the ability to visualize around corners [5,8,9]. As a result, its indications have expanded from cholesteatoma and stapes surgery to more complex procedures such as middle ear tumor excision and lateral skull base surgery, either via a total endoscopic approach or in combination with microscopic surgery [5,10,11]. GTT have as well been managed through an endoscopic approach and, since 2013, 13 studies have been published, to our knowledge, including 95 patients (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Otoendoscopes were also deemed aspirational at the primary level (Table 1 ), despite evidence demonstrating ergonomic benefits [ 50 ] and similar outcomes compared to traditional microscopic ear surgery [ 51 , 52 ]. This is perhaps due to its relatively recent arrival to the otology armamentarium and its steep learning curve for those trained only with operative microscopes to reliably benefit from the use of otology equipment [ 53 ]. It should be noted that at the tertiary level, only computer-assisted navigation for skull base surgery was deemed aspirational (Table 1 ).…”
Section: The Global Otolaryngology–head and Neck Surgery Initiative: ...mentioning
confidence: 99%